Soy Food Intake and Biomarkers of Breast Cancer Risk: Possible Difference in Asian Women?. (2nd January 2017) - Maskarinec, Gertraud; Ju, Dan; Morimoto, Yukiko; Franke, Adrian A.; Stanczyk, Frank Z.
ABSTRACT: Soy foods may protect against breast cancer in Asian but not in Western populations. We examined if the levels of various markers of breast cancer risk and inflammation, as well as the effects of soy food consumption on these markers, differ between Asian and non-Asian premenopausal women in two soy intervention trials. One study randomized 220 women to a 2-yr intervention and the other one randomized 96 women in a crossover design to examine the effects of consumption of 2 daily soy servings on nipple aspirate fluid (NAF) volume; estrogens in serum, NAF, and urine; insulin-like growth factor-1 (IGF-1), IGF-binding protein 3, and inflammatory markers in serum; and mammographic densities. Mixed linear models were applied to assess ethnic differences in biomarkers and response to the soy diet. Serum C-reactive protein, serum leptin, NAF volume, and NAF estrone sulfate were lower, while urinary isoflavones were higher in Asian than in non-Asian women. A significant interaction (pinteraction = 0.05) between ethnicity and soy diet was observed for IGF-1 but not for other biomarkers. The current findings suggest possible ethnic differences in levels of biomarkers for breast cancer risk but little evidence that Asian women respond differently to soy foods than non-Asian women.